RELATIONSHIP BETWEEN SERVANT LEADERSHIP AND EMPLOYEE SILENCE - Tan, Yushuang; Jiang, Haiyue (Journal of Buddhist Education and Research (JBER), 2024)
Traditional Chinese culture emphasizes harmony and loyalty, and enterprises are deeply influenced by traditional cultural values. Influenced by traditional Chinese culture which emphasizes collectivism, Chinese employees choose to remain silent in order to take the overall situation into consideration and to avoid being regarded as destroyers of organizational harmony due to their voice. To break employee silence and to encourage employees to give suggestions has become a key to organizational reform and innovation. That is why this paper aimed to investigate the mechanism of servant leadership as well as its effects on employee silence based on theories of voice efficacy and to construct a theoretical model of servant leader-voice efficacy and employee silence. The results revealed a negative correlation between servant leadership and employee silence in three dimensions. Voice efficacy was found to play a partially mediating role in such relationship. Organizational support positively moderated the positive correlation between service-oriented leadership and voice efficacy. Traditionality moderated the negative correlation between voice efficacy and employee silence.